Strategi Pengembangan Usaha Tembakau Rajangan pada Kelompok Tani Tegal Suci Desa Yangapi Kecamatan Tembuku Kabupaten Bangli - PUTRA, I GEDE WIRATHAMA BHASKARA; USTRYANA, I NYOMAN GEDE; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.1, Januari 2017DO - 10.24843/JAA.2017.v06.i01.p04, 2017)
Cut Tobacco Business Development Strategy in the Farmers Group of TelagaSuci, Village of Yangapi Sub-District of Tembuku Regency of Bangli This study aimed to find out alternative of cut tobacco business development strategyin the Farmers Group of Telaga Suci, Village of Yangapi, to identify how thestrengths, weaknesses, opportunities, and threats of the cut tobacco businessdevelopment at the Farmers Group ofTelaga Suci, Yangapi village. It was seen fromthe internal environment to find out the strengths and weaknesses, and the externalaspects to determine the opportunities and threats.The research location was in theFarmers Group of Telaga Suci, Village of Yangapi. The key informants in thisresearch were seven people. The key informants were determined deliberatelybecause the internal environment and the external environment of the cut tobaccobusiness in the Farmers Group ofTelaga Suci, of Yangapi Village was alreadyknown. This study used three kinds of analysis: analysis of the internal environment,external environment analysis and SWOT analysis (strengths, weaknesses,opportunities, threats).The cut tobacco business in the Farmers Group ofTelaga Sucihas been able to utilize the strength to overcome the weaknesses and to take theopportunity to address the threat. It was obtained five alternative strategies, namely:providing guidance to the group on how to manage the business and providingassistance of production facilities, development-oriented agribusiness to attractconsumers by utilizing the financial institution to increase capital, promotion topenetrate the wider market, making the rules of the group to overcome theconversionof farmland, and to improve the quality of tobacco in order to compete with othergroups of tobacco.
Keywords: tobacco, strategy, internal environment, external environment